Analisis Pengaruh Penggunaan Dennis Brown Splint Terhadap Penurunan Derajat Varus Pada Pasien Congenital Talipes Equino Varus Di Klinik Promedik Semarang - M Syafi’i; Siswiyanti Siswiyanti; Reni Faridastuti Indriyani (Jurnal Keterapian Fisik, 2016)
Abstract: CTEV, Dennis Brown Splint, Ponseti Metod. Congenital varus Talipes equino is one orthopedic congenital anomalies derived from the Latin talus (ankle), pes (foot), and equinus (resemble horse) is meant heel in plantar flexion and varus position means inversion and adduction. Maintenance by way of non-operative (manipulation and immobilization) and operative therapy. Non operative using the Ponseti method in which the cast performed serial and bracing. Bracing called dennis brown splint / foot abduction brace is used to maintain the foot in abduction and dorsiflexion position. To determine the effect of the use of dennis brown splint on the degree of varus in patients CTEV. This research is a retrospective case-control approach. Sampling using consecutive sampling. The subject of research as many as 15 samples. All samples are given modality busing dennis brown splint. Test requirements obtained by normality test p <0.05, so the data is not normally distributed, then the statistical analysis used was Wilcoxon. Wilcoxon statistical test showed that there was no effect of a decrease in the degree of varus with pre-post test without grouping right foot p = 0.103, and the grouping of the unilateral and bilateral leg on the right foot p = 0.317, p = 0.156 (p> 0.05), as well as pre -Post test without grouping on the left foot p = 0.044 (p <0.05) means that there is an influence, the grouping of the unilateral and bilateral leg on the left leg p = 0.102 and p = 0.151 (p> 0.05). According to the results of statistic analisis concluded there was no effect of the use of dennis brown splint to decrease the degree of varus in patients CTEV.